2001
DOI: 10.1055/s-2001-17375
|View full text |Cite
|
Sign up to set email alerts
|

Potential Role of Human Brain Microvascular Endothelial Cells in the Pathogenesis of Brain Abscess: Inhibition of Staphylococcus aureus by Activation of Indoleamine 2,3-Dioxygenase

Abstract: Cerebral abscess is a rare complication of staphylococcal septicemia in infants associated with high mortality and morbidity. In the pathogenesis of abscess formation, S. aureus, one major causative agent, interacts with endothelial cells of the brain vessels before reaching the central nervous system. This study examined the growth of S. aureus in human brain microvascular endothelial cells (HBMEC) cultures stimulated with cytokines. IFN-gamma inhibited S. aureus replication by the induction of indoleamine 2,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(44 citation statements)
references
References 28 publications
0
44
0
Order By: Relevance
“…Heyes et al (1997a) described IDO activity in human fetal mixed brain cells but without differentiating which cell types express IDO and produce QUIN. Within the human brain, cellular localization of IDO has been found in primary astrocytes, microvascular endothelial cells, microglia, and macrophages Guillemin et al, 2001Guillemin et al, , 2005bSchroten et al, 2001). We previously demonstrated and confirm here that primary human neurons express IDO and that the enzyme is inducible by IFN-␥ (Guillemin et al, 2005b).…”
Section: Discussionmentioning
confidence: 73%
“…Heyes et al (1997a) described IDO activity in human fetal mixed brain cells but without differentiating which cell types express IDO and produce QUIN. Within the human brain, cellular localization of IDO has been found in primary astrocytes, microvascular endothelial cells, microglia, and macrophages Guillemin et al, 2001Guillemin et al, , 2005bSchroten et al, 2001). We previously demonstrated and confirm here that primary human neurons express IDO and that the enzyme is inducible by IFN-␥ (Guillemin et al, 2005b).…”
Section: Discussionmentioning
confidence: 73%
“…On the basis of our previous identification of IDO as an IFNginducible T-cell inhibitory effector mechanism in human MSCs 2 and recent reports demonstrating antimicrobial activity of IDO expression in specific cell types 13,15 we first investigated, whether pro-inflammatory tissue cytokines such as TNFa and IL1b could induce or enhance IDO expression in human MSCs. As single agents both cytokines failed to stimulate detectable amounts of IDO activity, yet they significantly potentiated IFNginduced IDO activity and this effect was most pronounced with TNFa (Supplementary Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…Bacterial growth was determined photometrically or via colony counting after 16 h of culture in the absence of any antibiotics 13 while Toxoplasma gondii proliferation in MSC was assessed via parasite-specific uptake of 3 H-uracil during the last 24 h of a 4-day culture period. 14 Moreover, human MSC monolayer cultures were infected with human cytomegalovirus (CMV) at an multiplicity of infection of 0.015 and viral replication was assessed by analysis of CMV genome copy number using quantitative PCR after 3 days of culture.…”
Section: Western Blot Analysis For Human and Murine Ido And Inos Proteinmentioning
confidence: 99%
“…Additionally, we have recently shown that human astrocytoma cells exhibit strong IDO activation after stimulation with IFN-␥ (12). There is an increasing body of evidence indicating that IDO activation in human cells is a potent antiparasitic and antibacterial effector mechanism (7,9,10,11,27,33,39). That viruses are also controlled by IDO activation in human cells was first indicated by Bogdahi et al in 1999 (3).…”
Section: Gamma Interferon (Ifn-mentioning
confidence: 97%